2015
DOI: 10.1111/jopr.12345
|View full text |Cite
|
Sign up to set email alerts
|

Natural Tooth Color Estimation Based on Age and Gender

Abstract: In this sample of Caucasians from Spain, teeth became darker yellow and more reddish with increasing age. The L* coordinate is most strongly related to tooth color in aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
6
22
2
Order By: Relevance
“…The change detected was comparable with the color difference between 2 hue groups in the 3D shade guide (VITA Zahnfabrik, Bad Säckingen, Germany) and, therefore, slightly lower (Δ h° 2–2.4 units) than the hue change estimated on the basis of a cross‐sectional study (0.6 units/year × 8 years = 4.8 units). In contrast with previous reports, changes of lightness and chroma seem to be age‐cohort‐specific. Especially, a linear decrease of lightness and a linear increase of chroma during aging may be qualified by the recent data .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The change detected was comparable with the color difference between 2 hue groups in the 3D shade guide (VITA Zahnfabrik, Bad Säckingen, Germany) and, therefore, slightly lower (Δ h° 2–2.4 units) than the hue change estimated on the basis of a cross‐sectional study (0.6 units/year × 8 years = 4.8 units). In contrast with previous reports, changes of lightness and chroma seem to be age‐cohort‐specific. Especially, a linear decrease of lightness and a linear increase of chroma during aging may be qualified by the recent data .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with previous reports, changes of lightness and chroma seem to be age‐cohort‐specific. Especially, a linear decrease of lightness and a linear increase of chroma during aging may be qualified by the recent data . Whereas the teeth of the septuagenarians became more saturated—possibly giving the visual impression of becoming darker—clinically relevant darkening of 4 Δ L units was only observed for the teeth of quinquagenarians.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the contrary, the hue shift toward red was relatively small with increasing age. Previous studies reported that changes in b* variable increased by 0.10‐0.18 per year and L* variable decreased by 0.22‐0.28 per year . Although it might be difficult to compare directly with those studies, tooth color would shift toward yellow range by approximately 0.08‐0.13 b* units and darker by approximately 0.15‐0.16 L* units per year in this study.…”
Section: Discussionmentioning
confidence: 45%